2017
DOI: 10.1108/dlp-12-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

PlumX: a tool to showcase academic profile and distinction

Abstract: PurposeThe Saint Mary’s College of California (SMC) library plays an integral role in supporting one of the goals in the College’s Strategic Plan: “Raise the Academic Profile and Distinction”. This case study aims to assess the effectiveness of PlumX as a tool to showcase the academic profile and distinction of SMC. The library recognizes the importance of capturing impact of non-traditional creativity and engagement in addition to just traditional impact metrics of research. Design/methodology/approachThis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Trueger et al (2015) made a critical review of the Altmetric Score, although, it was Gumpenberger et al (2016) who expressed the strongest criticism of the Altmetric Score as impact indicator. In the case of PlumX, Champieux (2015) and Lindsay (2016) described the utilities of the service, while Wong and Vital (2017) analysed the implementation of the tool in a specific organization. However, no studies have been yet published about the functionality of CED due mainly to this product is still in beta.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trueger et al (2015) made a critical review of the Altmetric Score, although, it was Gumpenberger et al (2016) who expressed the strongest criticism of the Altmetric Score as impact indicator. In the case of PlumX, Champieux (2015) and Lindsay (2016) described the utilities of the service, while Wong and Vital (2017) analysed the implementation of the tool in a specific organization. However, no studies have been yet published about the functionality of CED due mainly to this product is still in beta.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it can be shown that PlumX Metrics also provides a competitive advantage to scientists who are more familiar with IT and web technologies and therefore can engage in gaming in social platforms in order to increase the significance of their research (Champieux, 2015;Wong & Vital, 2017).…”
Section: Plumx and Publons: Gaming With Altmetricsmentioning
confidence: 99%
“…Within the scholarly communications field, altmetrics have become a core competency for librarians and a popular topic in professional development (Cross, Oleen, & Perry, 2017;North American Serials Interest Group, 2017). Libraries have published on their experiences of integrating altmetrics with their IRs without delving into the systematic evaluation of altmetrics (Collister & Taylor, 2017;Wong & Vital, 2017). Even researchers selected IRs and libraries as the most trusted source of altmetrics (Zhang & Jackson, 2016).…”
Section: Altmetrics and Institutional Repositoriesmentioning
confidence: 99%